Understanding the relevance of Maulana Bhashani’s pedagogical philosophy in fostering social cohesion within contemporary educational landscape of Bangladesh - Raha, Samira Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2023.